METHODS OF PREVENTION OF PSYCHOLOGICAL DISEASE OF YOUTH STUDENTS - Samokhvalova, Anna; Tikhomirova , Elena; Vishnevskaya , Oksana; Shipova , Natalya; Smolina , Maria (Modern Psychology, 2023)
This article deals with the problem of the psychological well-being of student youth. The authors reveal the main factors that affect the psychological state of students, and also offer basic methods that can help students cope with emerging difficulties and improve psychological well-being. In particular, trainings with the use of "applied improvisation" are considered, aimed at developing the skills of positive thinking, communication and effective stress management. The article also reveals the importance of social support and interaction for the psychological well-being of students. In this direction, it is proposed to organize student associations and professional support groups. It is also recommended to establish psychological services at universities where students can get professional help. It is noted that a little-studied and underestimated disfactor of the psychological well-being of students is emotional burnout. In this regard, the issue of teaching students the skills of self-regulation is of great importance. The results of an empirical study aimed at studying the level of psychological well-being of students who combine studies at a university with professional activities are presented; a modern, effective tool for increasing the level of psychological well-being and developing self-regulation skills is proposed. The authors come to the conclusion that the use of a web service as a method of preventing ill-being will help increase the level of students’ awareness, develop the skills of self-control of the emotional state and form motivation for personal self-improvement. In conclusion, it was noted that the psychological well-being of students is an important, urgent problem that requires a systematic approach and comprehensive preventive measures based on the implementation of an individual approach.